1964
DOI: 10.1017/s0007485300049324
|View full text |Cite
|
Sign up to set email alerts
|

The biting habits of Aedes (Skusea) pembaensis Theo. and some other mosquitos of Faza, Pate Island, East Africa

Abstract: Descriptions are given of 24-hour biting catches, made in and around Faza, a village on Pate Island, off the north-east coast of Kenya, East Africa.Aedes pembaensis Theo. was the predominant mosquito in these catches but fair numbers of Aedes mombasaensis Mattingly were also taken; the biting cycles of these two are discussed. Six other species were taken in small numbers.For Ae. pembaensis, biting cycles calculated on catches grouped for site, moon phases, neap tides and spring tides show that both moon and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

1969
1969
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…In contrast to many of the foregoing examples van Someren & Furlong (1964) showed that on Pate Island, just off the Kenyan coast, moonlight had a pronounced effect on the biting times of Aedes pembaensis and Aedes mombasaensis. With Aedes pembaensis biting appeared to be enhanced by moonlight and inhibited by darkness and so biting was most intense in the early evening at· new moon and during the first quarter, times when the moon rose before sunset.…”
Section: Environmental Conditionscontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast to many of the foregoing examples van Someren & Furlong (1964) showed that on Pate Island, just off the Kenyan coast, moonlight had a pronounced effect on the biting times of Aedes pembaensis and Aedes mombasaensis. With Aedes pembaensis biting appeared to be enhanced by moonlight and inhibited by darkness and so biting was most intense in the early evening at· new moon and during the first quarter, times when the moon rose before sunset.…”
Section: Environmental Conditionscontrasting
confidence: 62%
“…The percentage biting at different levels can vary according to time. The species composition and biting cycles of the same species may differ according to locality, habitat and height (Galindo et al, 1950;Germain et al, 1972;Haddow, 1945b, 196Ia,b;Haddow & Ssenkubuge, 1965;Happold, 1965;Lumsden, 1958a;Rickenbach et al, 1971;van Someren & Furlong, 1964). In Zika forest, Uganda McCrae et al (1976) showed by 24-hr human bait catches that biting times of Anopheles implexus varied greatly according to different ecological zones.…”
Section: Location Of Bait Catchesmentioning
confidence: 99%
“…Furthermore, this behaviour may differ from one region to another. In South-East Asia, at Bangkok, SASA et al (1965b), observed that most females of C. p. The results recorded in Africa seem to show more uniform behaviour of C. p. quinquefasciatus, which is markedly endophagous in the Comoro Islands (BRUNHES, 1975), in East Africa ( VAN SOMEREN et al, 1958;SMITH, 1961;VAN SOMEREN and FURLONG, 1964) and in West Africa (SUBRA, 1972b). In Mayotte in the Comoro Islands, BRUNHES (1975) observed that the percentage of endophagous females could vary according to locality.…”
Section: Adultsmentioning
confidence: 96%
“…Similar observations have been made by other authors studying the biting cycle of endophagous females. Most biting specimens were collected after midnight in the Comoro Islands (BRUNHES, 1975), in East Africa ( VAN SOMEREN et al, 1958;TEESDALE, 1959;SMITH, 1961;VAN SOMEREN and FURLONG, 1964) and in West Africa (SUBRA, 1972b). In Reunion, however, HAMON (1965) observed most bites in the first part of the night.…”
Section: Adultsmentioning
confidence: 99%
“…inhabits the coast of East Africa and neighbouring islands in the Indian Ocean (Stone et al, 1959;Mattingly, 1963;Cogan et al, 1971). Information on the biology of this species is scarce but includes incidental observations of the breeding sites (van Someren & Furlong, 1964;Hopkins, 1952) and the periodicity of biting (i.e., landing) by blood-seeking females (Lumsden, 1955;van Someren et al, 1958;van Someren & Furlong, 1964). Until recently, A. fryeri has been confused with A. mombasaensis Mattingly, as a result of an incorrect assignment to A. fryeri of two larvae from Aldabra Island (Hopkins, 1936); these larvae were subsequently shown to be Aedimorphus, and A. mombasaensis (under which name some of the biting studies appear) has fallen as a synonym of A. fryeri (van Someren, 1972).…”
Section: Introductionmentioning
confidence: 99%